THE UTILIZATION OF THE YOUTUBE CHANNEL “LEARN ARABIC WITH KHASU” AS A RESOURCE FOR VOCABULARY MASTERY - Ayu Miranda; Okita Fatma Marliana; Dedi Hidayat (Kitaba, 2024)
Arabic language learning in the digital era is very important to always innovate. The utilization of social media, especially Youtube, provides a new face regarding student learning facilities. The learning process seems to have unique characteristics, where students can not only get learning at school, but can be done anywhere, anytime when the students feel comfortable to learn. This research aims to describe how to utilize khasu YouTube channel in the vocabulary learning process. The type of data used in this research is descriptive qualitative with the content analysis method. from the results of the discussion, vocabulary learning will become more interesting if the teacher uses YouTube as a means to improve vocabulary mastery.